Health Family Indicators in North Lombok Regency - Yogi Fitriadi; Noor Afif Mahmudah; Mumtihana muchlis; Cornelia Wahyu danawati; Wahyudi Istiono; Mora Claramita; Adi Heru Sutomo; Hari Kusnanto Josef (Review of Primary Care Practice and Education (Kajian Praktik dan Pendidikan Layanan Primer), 2023)
Background: Health family indicators are twelve indicators used to assess family health status. The increase in the health family indicator is one of the parameters of The Indonesia Health Program with a Family Approach (PIS-PK) success. This health family indicator can increase if there is an increase in public awareness of family health and the right policies from the health service or government in an area related to health. To make an appropriate policy, accurate health family indicator survey data is needed that can be used as a guideline to make health-related policies and implement health policies in accordance with problems in the community based on the results of the health family indicator survey, especially for family with vulnerable groups in the context of post disaster/crisis phase. Objectives: This study aims to assess the achievement of health family indicator in North Lombok Regency. This study is the first to be conducted with the aim of describing the health family indicator achievement of families who have family members with vulnerable groups in post disaster/crisis phase. Method: This study is a descriptive study that assesses the health status of families in the North Lombok Regency area. The subject of the study was a family that had family members with vulnerable groups selected by purposive sampling. Data retrieval was conducted by interviewing participants who met the criteria for inclusion and exclusion with the guidance of healthy family indicator questionnaires by trained cadres. The data obtained was analyzed using Microsoft Excel and STATA 16 programs. Result: 292 families in six village met the criteria for inclusion and exclusion. The results of this study showed that 6.51% of family respondents belonged to the category of unhealthy families, 57.53% were pre-healthy families and 35.96% were healthy families. The highest percentage of healthy families is in Santong village (44.93%, n = 69) while the highest percentage of unhealthy families is in Santong Mulia village (19.23%, n = 26). The average percentage of healthy families in six villages is 34.02% while the average percentage of unhealthy families is 8.53%. Conclusion: Most families with vulnerable groups in the North Lombok Regency are pre-healthy families.